A Pan-Genomic Approach to Understand the Basis of Host Adaptation in Achromobacter. (1st April 2017) - Jeukens, Julie; Freschi, Luca; Vincent, Antony T.; Emond-Rheault, Jean-Guillaume; Kukavica-Ibrulj, Irena; Charette, Steve J.; Levesque, Roger C.
Abstract : Over the past decade, there has been a rising interest in Achromobacter sp., an emerging opportunistic pathogen responsible for nosocomial and cystic fibrosis lung infections. Species of this genus are ubiquitous in the environment, can outcompete resident microbiota, and are resistant to commonly used disinfectants as well as antibiotics. Nevertheless, the Achromobacter genus suffers from difficulties in diagnosis, unresolved taxonomy and limited understanding of how it adapts to the cystic fibrosis lung, not to mention other host environments. The goals of this first genus-wide comparative genomics study were to clarify the taxonomy of this genus and identify genomic features associated with pathogenicity and host adaptation. This was done with a widely applicable approach based on pan-genome analysis. First, using all publicly available genomes, a combination of phylogenetic analysis based on 1, 780 conserved genes with average nucleotide identity and accessory genome composition allowed the identification of a largely clinical lineage composed of Achromobacter xylosoxidans, Achromobacter insuavis, Achromobacter dolens, and Achromobacter ruhlandii . Within this lineage, we identified 35 positively selected genes involved in metabolism, regulation and efflux-mediated antibiotic resistance. Second, resistome analysis showed that this clinical lineage carried additional antibiotic resistance genes compared with other isolates. Finally, we identified putative mobile elements that contribute 53% of the genus's resistome and support horizontal gene transfer between Achromobacter and other ecologically similar genera. This study provides strong phylogenetic and pan-genomic bases to motivate further research on Achromobacter, and contributes to the understanding of opportunistic pathogen evolution.